Адміністративно-правовий статус господарських судів: сутність і зміст - Шатерніков, М. І.; Shaternikov, M. I. (Право і Безпека. - 2016. - № 2 (61). - С. 60–64., 2016)
Розглянуто наявні у правознавстві погляди на зміст та сутність поняття «адміністративно-правовий статус», акцентовано увагу на його структурних елементах – правоздатності, дієздатності, деліктоздатності й компетенції. З’ясовано сутність кожного з цих елементів стосовно адміністративно-правового статусу господарських судів. Наголошено на тому, що адміністративно-правовий статус господарських судів необхідно розглядати з урахуванням того, що такі органи є юридичними особами публічного права. Дано авторське бачення сутності поняття «адміністративно-правовий статус господарських судів».

Existing in jurisprudence points of view on the content and essence of the concept of «administrative and legal status» have been considered; special attention has been focused on its structural elements – legal capacity, legal capability, passive dispositive capacity and competence. The essence of each of these elements in relation to administrative and legal status of the economic courts has been found out. It has been emphasized that administrative and legal status of economic courts should be considered taking into account the fact that such bodies are legal entities of public law. It has been indicated that administrative and legal status should be considered as a system of features of a subject, as legal status of the subject and as a set of rights and obligations of the subject, on which this administrative and legal status is consolidated. The author’s vision of the essence of the concept of “administrative and legal status of economic courts” has been provided. The author offers to understand it as a set of features established in the norms of administrative law that considering the tasks, functions and powers of these bodies determine their legal status among other subjects of administrative and legal relations. It has been established that the foundation and integral element of administrative and legal status of economic courts is their administrative legal personality, under the presence of which those public authorities can acquire the said status and become real participants of administrative legal relations.

Рассмотрены существующие в правоведении взгляды на содержание и сущность понятия «административно-правовой статус», акцентировано внимание на его структурных элементах – правоспособности, дееспособности, деликтоспособности и компетенции. Выяснена сущность каждого из этих элементов по отношению к административно-правовому статусу хозяйственных судов. Отмечено, что административно-правовой статус хозяйственных судов необходимо рассматривать с учётом того, что такие органы являются юридическими лицами публичного права. Предоставлено авторское видение сущности понятия «административно-правовой статус хозяйственных судов».
Administrative and legal status of economic courts: essence and content
Административно-правовой статус хозяйственных судов: сущность и содержание
Шатерніков, М. І. Адміністративно-правовий статус господарських судів: сутність і зміст / М. І. Шатерніков // Право і Безпека. - 2016. - № 2. - С. 60-64.
Шатерніков М. І. "Адміністративно-правовий статус господарських судів: сутність і зміст." Право і Безпека 2 (2016): 60-64.
Shaternikov, M.I. (2016), “Administrative and legal status of economic courts: essence and content” [“Administratyvno-pravovyi status hospodarskykh sudiv: sutnist i zmist”], Pravo i Bezpeka, No. 2, pp. 60–64.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; правовий статус; адміністративно-правовий статус; господарські суди; правоздатність; дієздатність; деліктоздатність; компетенція; legal status; administrative and legal status; economic courts; legal capacity; legal capability; passive dispositive capacity; competence; правовой статус; административно-правовой статус; хозяйственные суды; правоспособность; дееспособность; деликтоспособность; компетенция